Development of junior middle distance runners - Sherman, C. (Modern Athlete & Coach, 2013)
Introduction The purpose of this article is to assist coaches and readers with information relevant to the development of junior athletes specialising in the 800m to 3000m. It includes some training program samples and information to hopefully motivate athletes. It assumes that the athletes referred to in this paper have completed the necessary (IAAF) three years of competing in the Little Athletic before deciding to choose distance running. It also assumes that athletes are approximately 13 years of age or older, are just reaching maturity and are having their teenage growth spurt. I mention this because it can be assumed that they cannot cope with a) a periodised program and b) an adult program which assumes juniors all have not developed an internal lactic acid buffering system. That is, these little people have the capability to produce lactic acid but not tolerate it due to their buffering system not having developed. As you know, this occurs about 12 months after boys reach their maximum height velocity during puberty and girls at their maximum height velocity. Therefore, this paper will not include the typical adult lactic acid producing workouts such as short recovery 400m repetitions.